2014
DOI: 10.2334/josnusd.56.59
|View full text |Cite
|
Sign up to set email alerts
|

Root proximity and stability of orthodontic anchor screws

Abstract: This study aimed to investigate a causal relationship between the stability of orthodontic anchor screws (screws) and the degree of their proximity to the root (root proximity) using mobility test device (Periotest) and cone-beam computed tomography (CBCT). In total, 165 (diameter 1.6 mm; length 8 mm) screws in 58 patients (average age, 24.4 ± 8.5 years) were evaluated. After screw placement, CBCT was used for diagnostic imaging of the area around the site. Root proximity was evaluated and categorized into thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
1
13
0
1
Order By: Relevance
“…The Periotest device was developed to measure mechanical retention between bone and dental implants. Using PTVs obtained after placement, Shigeeda (28) found that mini-screws had greater mobility, which can result in failure regardless of root proximity. Inaba (23) reported a strong correlation between screw-bone contact state and PTV and concluded that PTV was an appropriate index of screw stability.…”
Section: Discussionmentioning
confidence: 99%
“…The Periotest device was developed to measure mechanical retention between bone and dental implants. Using PTVs obtained after placement, Shigeeda (28) found that mini-screws had greater mobility, which can result in failure regardless of root proximity. Inaba (23) reported a strong correlation between screw-bone contact state and PTV and concluded that PTV was an appropriate index of screw stability.…”
Section: Discussionmentioning
confidence: 99%
“…Screws that contacted the tooth root were removed and defined as failures when the patient experienced clinical manifestations such as pain and discomfort or when there was mobility of the screw. According to Shigeeda,27 screws that contacted the tooth root without root injury were not considered failures and were kept under observation.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, if the micro-screws are too close to the root, they will cause loosening and shedding, resulting in failure of the implantation surgery and damage to other important anatomical structures due to incorrect positioning. Therefore, the micro-screw should be positioned in the central area between the two roots to ensure the continuity and stability of the anchor [21][22][23] . In clinical practice, it is necessary to consider the proper safety range of both the alveolar bone and the soft tissue.…”
Section: Discussionmentioning
confidence: 99%